(untitled) (Proceedings of International Conference on Special Education, 2017)
Inclusive Education is a worldwide program in special education which aims for Education For All (EFA). The Philippines’ Department of Education continuously supports inclusive education and promotes inclusion of children with special needs in all public and private schools across the country. Moreover, the Philippines’ DepEd’s Pangasinan Division II implements inclusive education but faces many challenges in the implementation in all schools over the years. To strengthen and to bring inclusion in action, Pangasinan Division II gears towards the implementation of several activities for students, both in typical, mainstream and special education class, professional upgrading and developments for regular and special education teachers, involvement activities for parents, stakeholders and the entire community to fully embrace and implement inclusive education. As a result, inclusive education, through working together, provides a great positive impact to the learners, strong support from parents and awareness to the whole community. This paper presentation aims to provide the participants with practical, evidenced-based and best practices towards inclusive education